(untitled) (Scientific Journal of Actuarial Finance and Accounting, 2024)
Recently, there have been significant changes in the provision of remote banking services in commercial banks. As a result, commercial banks are conducting explanatory work for their clients on how to use these services, which will lead to their further popularization in the future. This article presents conclusions and recommendations regarding the modern methods of providing remote banking services in the operations of commercial banks and ways to improve them.